2013
DOI: 10.1007/s10493-012-9651-9
|View full text |Cite
|
Sign up to set email alerts
|

Potential geographical distribution of the red palm mite in South America

Abstract: Among pests that have recently been introduced into the Americas, the red palm mite, Raoiella indica Hirst (Prostigmata: Tenuipalpidae), is the most invasive. This mite has spread rapidly to several Caribbean countries, United States of America, Mexico, Venezuela, Colombia and Brazil. The potential dispersion of R. indica to other regions of South America could seriously impact the cultivation of coconuts, bananas, exotic and native palms and tropical flowers such as the Heliconiaceae. To facilitate the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…Although failure to find R. indica in some sampling areas could be by chance, its absence in areas of southern Brazil (Rio Grande do Sul, Santa Catarina, and part of Paraná States) could reflect the ecological unsuitability of those places. These results fit well with what was predicted by the model developed by Amaro & Morais (2013), based on 20 environmental variables. The authors concluded that the variables that most influenced their prediction were related to temperature.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Although failure to find R. indica in some sampling areas could be by chance, its absence in areas of southern Brazil (Rio Grande do Sul, Santa Catarina, and part of Paraná States) could reflect the ecological unsuitability of those places. These results fit well with what was predicted by the model developed by Amaro & Morais (2013), based on 20 environmental variables. The authors concluded that the variables that most influenced their prediction were related to temperature.…”
Section: Discussionsupporting
confidence: 86%
“…An examination of the historical records (Continente 2018) showed that average minimum monthly temperatures in places where R. indica was found in northern Paraná are at least 9 °C, except Maringá (7.2 °C), whereas in places where it was not found, temperatures are at most 9 °C, except Morretes, Palotina, Pontal do Paraná,and Terra Roxa (12.3,9.6,13.7,and 9.8 °C, respectively). However, according to that the study of Amaro & Morais (2013), it is still possible that the mite could be found further south, along the coast of Rio Grande to Sul and Santa Catarina, areas not surveyed in this work. Also, according to that study, R. indica is expected to be able to extend south of the maximum latitude where it was detected dur-ing the current study (Iporã), in neighboring Paraguay and Argentina, along the low lands of the Paraguay River basin.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Because the prevailing climatic conditions of low rainfall and high temperature are favorable for the development of the red palm mite (Nagesha-Chandra & Channabasavanna 1983;Taylor et al 2012), introduction of the red palm mite to northeastern Brazil, which is the major regional producer of coconuts, is likely to significantly impact the coconut industry in the region Gondim et al 2012;Amaro & Morais 2013).…”
mentioning
confidence: 99%
“…In Brazil, it is considered a quarantine pest and has been reported in the states of Roraima (Navia et al, 2011) and Amazonas (Rodrigues & Antony, 2011). Raoiella indica has a high potential to establish itself and to cause serious ecological and economic impacts in the country, particularly on coconut, banana, native palms, and flowers of the Heliconiaceae family (Amaro & Morais, 2013).…”
Section: Amblyseius Largoensis In Controlling Red Palm Mite Under Semmentioning
confidence: 99%